2022
DOI: 10.1016/s2352-3026(21)00381-1
|View full text |Cite
|
Sign up to set email alerts
|

Melflufen or pomalidomide plus dexamethasone for patients with multiple myeloma refractory to lenalidomide (OCEAN): a randomised, head-to-head, open-label, phase 3 study

Abstract: Background Melphalan flufenamide (melflufen), an alkylating peptide-drug conjugate, plus dexamethasone showed clinical activity and manageable safety in the phase 2 HORIZON study. We aimed to determine whether melflufen plus dexamethasone would provide a progression-free survival benefit compared with pomalidomide plus dexamethasone in patients with previously treated multiple myeloma. MethodsIn this randomised, open-label, head-to-head, phase 3 study (OCEAN), adult patients (aged ≥18 years) were recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…A single‐arm phase II trial 50 demonstrated an ORR of 26% in patients with TCR MM treated with melflufen plus dexamethasone, but with a short PFS and substantial haematological toxicity. Melflufen was transiently available in the USA after receiving accelerated approval but has since been voluntarily withdrawn from the market given the higher number of deaths than in the control arm in a confirmatory phase III trial 51 …”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single‐arm phase II trial 50 demonstrated an ORR of 26% in patients with TCR MM treated with melflufen plus dexamethasone, but with a short PFS and substantial haematological toxicity. Melflufen was transiently available in the USA after receiving accelerated approval but has since been voluntarily withdrawn from the market given the higher number of deaths than in the control arm in a confirmatory phase III trial 51 …”
Section: Treatment Optionsmentioning
confidence: 99%
“…Melflufen was transiently available in the USA after receiving accelerated approval but has since been voluntarily withdrawn from the market given the higher number of deaths than in the control arm in a confirmatory phase III trial. 51 In essence, alkylator-based regimens are often deployed in patients with TCR MM particularly in those with rapidly progressing disease. They offer a reasonable chance of short-term disease control, yet with substantial toxicity.…”
Section: Chemotherapy-based Regimensmentioning
confidence: 99%
“…Although meflufen was initially granted accelerated FDA approval based on the HORIZON phase 2 study (NCT02963493), 85,86 FDA has since suspended enrollment to meflufen clinical trial based on the OCEAN phase 3 study, which evaluated the efficacy and safety of melfufen‐dexamethasone versus pomalidomide‐dexamethasone, as the study reported increased risk of death in the meflufan arm, and the study was terminated early. The investigators speculated that the poor OS in the melflufen group, among those with previous exposure to high‐dose melphalan (i.e., the autologous hematopoietic stem cell transplant subgroup), probably resulted from resistance to high‐dose alkylator therapy and an already compromised marrow reserve at study entry, making melflufen, with its attendant severe hematological toxicities, less tolerable 87,88 …”
Section: Current Treatment Paradigmmentioning
confidence: 99%
“…: Md ( n = 157) 5 (r. 2–12) 64, 97, 80 13% ref. to melphalan 14 29%, 1% 4.2 (95% CI 3.4–4.9) Median time to ≥ PR: 1.9 (r. 1–7.4) OCEAN [ 2 ] Prior exposure: I: Md ( n = 249) C: Pd ( n = 249) I: 3 (IQR 2–3) C: 3 (IQR 2–3) I: 66, 100, 20 C: 65, 100, 16 I: 19.8 C: 18.6 I: 33%, 3% C: 27%, 1% I: 6.8 (95% CI 5.0–8.5) C: 4.9 (95% CI 4.2–5.7) I: 2.1 (IQR 1.1–3.7) C: 2.0 (IQR 1.1–2.9) Selinexor STORM [ 3 ] Sd ( n = 122) 7 (range 3–18) Prior ref. : 100, 100, 100 - 26%, 2% 3.7 (95% CU 3–5.3) - STOMP [ 4 ] SVd ( n = 42) 3 (range 1–11) PI ref.…”
Section: Introductionmentioning
confidence: 99%